Lipid-laden partially-activated plasmacytoid and CD4-CD8a+ dendritic cells accumulate in tissues in elderly mice - Gardner, Joanne; Mamotte, Cyril; McGonigle, T.; Dye, Danielle; Jackaman, Connie; Nelson, Delia (BioMed Central Ltd., 2014)
Background - Aging is associated with a decline in lymphocyte function however, little is known about dendritic cell (DC) subsets and aging. Aging is also associated with increasing circulating lipid levels and intracellular lipid accumulation modulates DC function. Whether age-associated increases in lipid levels influence DC biology is unknown. Thus, the effects of aging on DC subsets were assessed in vivo using young adult and elderly C57BL/6 J mice. Results - Major age-related changes included increased CD11c+ DC numbers in lymph nodes, spleens and livers, but not lungs, and significantly increased proportions of plasmacytoid (pDC) and CD4-CD8α+ DCs in lymph nodes and livers. Other changes included altered pDC activation status (decreased CD40, increased MHC class-I and MHC class-II), increased lipid content in pDCs and CD4-CD8α+ DCs, and increased expression of key mediators of lipid uptake including lipoprotein lipase, scavenger receptors (CD36, CD68 and LRP-1) in most tissues. Conclusions - Aging is associated with organ-specific numerical changes in DC subsets, and DC activation status, and increased lipid content in pDCs and CD4-CD8α+ DCs. Up-regulation of lipoprotein lipase and scavenger receptors by lipid-rich pDCs and CD4-CD8α+ DCs suggests these molecules contribute to DC lipid accumulation in the elderly. Lipid accumulation and modulated activation in pDCs and CD4-CD8α+ DCs may contribute to the declining responses to vaccination and infection with age.